Assessment of strain-induced cavitation of silica-filled styrene-butadiene rubber nanocomposite by synchrotron radiation tomography. (December 2022) - Federico, Carlos Eloy; Fleming, Yves; Kotecký, Ondřej; Rommel, Robert; Philippe, Adrian-Marie; Westermann, Stephan; Addiego, Frédéric
Abstract: Synchrotron radiation micro-computed tomography (SR μCT) was employed to study the cavitation phenomena upon cyclic tensile loading prior to and after thermal exposure of silica-filled styrene-butadiene rubber nanocomposites cured at different temperatures. A comparison with laboratory μCT measurements was also conducted to extend previous knowledge acquired by laboratory μCT into high resolution. SR μCT enhanced the detection of fillers and cavities down to dimensions of 3 μm, which represents a meaningful contribution to elucidate and characterize physical phenomena affecting the mechanical durability of rubber nanocomposites. The main findings revealed that the initiation of cavitation could be classified as: (a) debonding at the agglomerate's poles, (b) internal agglomerate fracture and (c) combination of debonding at the poles and internal agglomerate fracture. Cavitation in the rubber composite cured at 150 °C was dominated by debonding at the agglomerate poles, whereas cavitation in the rubber composite cured at 170 °C was evenly dominated among the three categories. Thermal exposure was found to increase the apparent crosslinking density of the rubber matrix thus inducing an increase of the stiffness of the nanocomposite in one hand and a decrease of its rupture strain. SR μCT revealed that fewer cavities were initiated in these samples, but their size was larger in comparison with the non-thermally treated samples.